1984
DOI: 10.1159/000233602
|View full text |Cite
|
Sign up to set email alerts
|

Oral Induction of the Secretory Antibody Response by Soluble and Particulate Antigens

Abstract: The ability of gastric intubation of a soluble or a particulate form of dinitrophenylated bovine γ-globulin (DNP-BGG) to induce salivary IgA antibody was examined. Gastric intubation of the particulate form of the antigen tended to induce a greater response than did equivalent doses of the soluble form. However, systemic immunization with the soluble form of the antigen prior to gastric intubation of antigen increased the salivary IgA response. Prior systemic injection of the particulate form did not increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 14 publications
2
18
1
Order By: Relevance
“…Nevertheless, adjuvant appears to be a requirement for an effective immune response against those antigens (30)(31)(32)(33). On the other hand, presentation of antigen as a constituent of bacteria or virus particles significantly enhances the immune response to the antigen (34,35). We have demonstrated that vaccine antigens can be expressed in an immunogenic form using engineered plant virus (7).…”
mentioning
confidence: 99%
“…Nevertheless, adjuvant appears to be a requirement for an effective immune response against those antigens (30)(31)(32)(33). On the other hand, presentation of antigen as a constituent of bacteria or virus particles significantly enhances the immune response to the antigen (34,35). We have demonstrated that vaccine antigens can be expressed in an immunogenic form using engineered plant virus (7).…”
mentioning
confidence: 99%
“…More specif ically, it has been demonstrated that saliva [I, [6][7][8][9] and milk [10][11][12][13][14] are sources of IgA antibody follow ing ingestion of an antigen. Prior investigations in our laboratory have demonstrated that ingestion of a par ticulate form of a DNP antigen elicits a greater sali vary IgG response than does ingestion of a soluble form [15]. However, we have found that remote injec tion of the soluble form of a DNP antigen is generally more effective at eliciting a remote secretory site IgG response than is remote injection of the particulate form of the antigen [16,17], In 1964, it was observed by Gowans and Knight [ 18] that large lymphocytes from thoracic duct lymph did not recirculate through the bloodstream, but migrated to the gut lamina propria.…”
Section: Introductionmentioning
confidence: 92%
“…It has been shown recently that mice primed by subcutaneous injection of allergens develop a signifi cant anamnestic response following oral boosting [5], and other work [2] has demonstrated that optimal in duction of antibody, including secretory IgA at mu cosal surfaces, is achieved in rats by oral dosing fol lowing parenteral priming. A similar effect on the in duction of grass pollen extract-specific serum anti body was observed in this study.…”
Section: Days After Subcutaneous Injectionmentioning
confidence: 99%